Evaluating cost and resource use associated with pulse oximetry screening for critical congenital heart disease: Empiric estimates and sources of variation. Issue 11 (28th July 2015) - Reeder, Matthew R.; Kim, Jaewhan; Nance, Amy; Krikov, Sergey; Feldkamp, Marcia L.; Randall, Harper; Botto, Lorenzo D.
Abstract : Background: Newborn screening for critical congenital heart disease (CCHD) using pulse oximetry is being implemented in the United States and internationally; however, few data are available on the associated in‐hospital costs and use of resources. Methods: Time and motion study in well‐baby nurseries at two large urban hospitals in Utah using different approaches to pulse oximetry screening. Two observers recorded the time for each screening step together with provider and equipment characteristics. Structured questionnaire provided additional information on labor and equipment costs. Results: Fifty‐three CCHD screens were observed. At site A ( n = 22), screening was mostly done by medical assistants (95%) using disposable probes (100%); at site B ( n = 31), screening was mostly performed by certified nursing assistants (90%) using reusable probes (90%). Considering only first screens ( n = 53), the median screen time was 8.6 min (range: 3.2–23.2), with no significant difference between sites. The overall cost ($ in 2014) of screening per baby was $24.52 at site A and $2.60 at site B. Nearly all the variation in cost (90%) was due to the cost of disposable probes; labor costs were similar between sites. Conclusion: CCHD screening by means of pulse oximetry is reasonably fast for most babies, leading to relative small labor costs with little variation by provider type. The main driver of costs is equipment: in a high throughput setting, reusable probes are currently associated with considerable cost saving compared with disposable probes. As programs expand to universal screening, improved and cheaper technologies could lead to considerable economies of scale. Birth Defects Research (Part A), 2015. © 2015 Wiley Periodicals, Inc. Birth Defects Research (Part A) 103:962–971, 2015. © 2015 Wiley Periodicals, Inc.